Distribution and Abundance of MAAs in 33 Species of Microalgae across 13 Classes - Llewellyn, Carole Anne (Molecular Diversity Preservation International, 2010)
We provide a direct comparison of the distribution and abundance of mycosporine-like amino acids (MAAs) in a diverse range of microalgal cultures (33 species across 13 classes) grown without supplementary ultraviolet radiation (UV). We compare the MAAs in cultures with those present in characterised natural phytoplankton populations from the English Channel. We detected 25 UV absorbing compounds including at least two with multiple absorption maxima. We used LC-MS to provide chemical characterisation of the six most commonly occurring MAAs, namely, palythene, palythine, mycosporine-glycine, palythenic acid, porphyra-334 and shinorine. MAAs were abundant (up to 7 pg MAA cell(−1)) in 10 species, with more minor and often unknown MAAs in a further 11 cultures. Shinorine was the most frequently occurring and abundant MAA (up to 6.5 pg cell(−1)) and was present in all but two of the MAA-containing species. The study provides further insight into the diversity and abundance of MAAs important from an ecological perspective and as potential source of natural alternatives to synthetic sunscreens.